Correlation between Nutritional Status, Blood Pressure, Cholesterol Levels, and Cognition in Middle-Aged Adults at Sedati Subdistrict, Sidoarjo - Aulia, Salma Shafrina; Mayumi Aisyah Lady; Choirul Anna Nur Afifah; Cleonara Yanuar Dini (Indonesian Journal of Human Nutrition, 2025)
The increasing population of pre-elderly individuals presents emerging challenges in maintaining quality of life, particularly regarding age-related cognitive decline. Previous studies have examined factors such as nutritional status, blood pressure, and total cholesterol levels; however, their findings remain inconsistent. This study examines the correlation between nutritional status, blood pressure, and total cholesterol levels with cognitive function in middle-aged individuals in Sedati Subdistrict, Sidoarjo. This quantitative study used a cross-sectional design and involved 107 respondents aged 45-59 years selected through consecutive sampling. Data collection included Body Mass Index (BMI) measurements, blood pressure and total cholesterol levels assessments, and interviews using the Mini-Mental State Examination (MMSE) questionnaire. Statistical analysis was conducted using Spearman’s Rank correlation test. The results showed that the majority of respondents were classified as overweight (71%), hypertensive (52%), with high total cholesterol levels (61%), and normal cognitive function (51%). Spearman’s Rank test result indicated no significant correlation between nutritional status (p=0.488), blood pressure (p=0.778), and total cholesterol levels (p=0.939) with cognitive function. This study concludes that no significant correlation was found between nutritional status, blood pressure, and total cholesterol levels with cognitive function in middle-aged individuals in Sedati Subdistrict, Sidoarjo.